Społeczne przesłanie prośby „chleba naszego powszedniego daj nam dzisiaj” w komentarzach Ojców Kościoła do Modlitwy Pańskiej - Wygralak, Paweł (Vox Patrum, 2014)
The article discusses the problem of social message of the Fourth Petition in the Lord’s Prayer: “Give us this day our daily bread”. As Fathers of the Church comment on the content of the request, they find its fulfillment “in the hands” of the Christian themselves. This prayer will be answered insofar as the one in prayer adopts the right attitude towards material goods. According to the most ancient commentators, Disciple of Christ should care only about what is indispensable for everyday life. In addition, it is important to ask for bread only “this day” whereas “tomorrow” should be entrusted to God’s Providence. Here they often like to appeal to the Christ’s parable of the rich man, who yielded an abundant harvest (Lk 12, 16-20). Few Fathers, especially Cyprian of Carthage, Gregory of Nyssa and Pseudo-Chrysostom point out that the request for daily bread demands the active help to the needy, as well as the prevention of all forms of social injustice.